6, 6′-(Perfluoropropane-2, 2-diyl)bis(2, 3-dihydrophthalazine-1, 4-dione)-based coordination polymers and their sensing properties towards Cr2O72−. Issue 19 (25th April 2019) - Wan, Ke-Ke; Yu, Jie-Hui; Xu, Ji-Qing
Abstract : The structures of six new diacylhydrazidate-based coordination polymers were reported. Based on their better photoluminescence properties, their sensing abilities towards Cr2O7 2− were investigated. Abstract : Through employing the hydrothermal in situ acylation of organic acids with N2 H4, six L1 2− -based coordination polymers, [M(L1)(H2 O)]·H2 O (M 2+ = Cd 2+ 1, Zn 2+ 2, Fe 2+ 3, Mg 2+ 4 ; H2 L1 = 6, 6′-(perfluoropropane-2, 2-diyl)bis(2, 3-dihydrophthalazine-1, 4-dione)), [Pb(L1)]5, and [Er2 (L1)2 (ox)(H2 O)2 ]·5H2 O (ox = oxalate)6, were obtained. X-ray single-crystal diffraction analysis reveals that (i) the L1 2− -based Cd 2+, Zn 2+, Fe 2+ and Mg 2+ coordination polymers are isostructural, and they possess a 2D single-layer network structure with a 4 4 topology; (ii)5 possesses a 3D network structure, which is constructed from the dinuclear Pb2 O8 12− clusters by the L1 2− molecules; (iii)6 possesses a 2D double-layer network structure. Two 2D single-layer networks (the same as those in1–4 ) are supported by ox to form this 2D double-layer network. 1D channels (428.9 Å 3 for total potential solvent-accessible void volume) are observed in6 .1, 2, 5 and6 are found to emit blue light, corresponding to the L1 2− -centered electronic excitation. Based on the photoluminescence properties, their sensing ability towards the inorganic Cr2 O7 2− anion was investigated.5 exhibits the better sensing ability towards Cr2 O7 2− . The heavy-atom effect should play a key role.